Mapping the Research on Entrepreneurial Competencies in Relationship with Higher Education Institutions - Carmen Florina FAGADAR; Diana Teodora TRIP; Daniel BADULESCU (Communications of International Proceedings, 2021)
In entrepreneurship education, conventional wisdom is that educational institutions have a significant role in the formation of entrepreneurial competencies. However, the vigorous and multifaceted discussions on entrepreneurship and the mixed signals received from the market regarding the ultimate effectiveness of such transformational endeavors open the way for more extensive research. From complex, multilayered concepts' development to longitudinal studies' assessment, the burgeoning literature has a multitude of nuances for which to mine. Thus, to map the state of the art of this dual research field and condense relevant emerging patterns, this paper intends to develop new bibliometric insights and trace an agenda for further inquiry into significant and relevant topics. The study employed bibliometric methods to map out the knowledge base and made use of HistCite and VosViewer for this purpose. The Web of Science platform was interrogated, and it yielded a relevant sample of peer-reviewed articles on which a series of bibliometric analyses were performed. The results indicate that this field is based on three interlinked clusters which offer a better understanding of the research streams permeating the field, as well as the gaps, and future research trends.
Keywords: Entrepreneurship Education; entrepreneurial competencies; higher education institutions; HEI; bibliometrics.